Lepidorbitoides (Foraminifera) from the lower Maastrichtian Kallankuruchchi Formation, Cauvery Basin, India: Morphometry and paleobiogeography. (September 2017) - Malarkodi, Nallamuthu; Özcan, Ercan; Venkataraman, Deepak; Chandra Somappa, Subhash; Gowda, Suresha; Kumar Tindlu Nagaraja, P.; Yücel, Ali Osman
Abstract: The southernmost occurrence of the early Maastrichtian larger benthic foraminifera (LBF) in Tethys is known from the Kallankuruchchi Formation in the Cauvery Basin, SE India, represented by Lepidorbitoides - Siderolites assemblages. The systematics, age and paleobiogeography of Lepidorbitoides here have as yet remained unresolved due to lack of information particularly on the nepionic arrangement, whereas their links with the Western Tethyan and Caribbean biogeographic domains were speculated. Lepidorbitoides, studied from the same level in seven samples in two separate areas, invariably possess quadriserial nepionts and adauxiliary chamberlets, whose mean number ranges from 3.79 to 4.67. The ratio between the sample means of the internal diameter of deuteroconch and protoconch varies between 1.72 and 1.86. The equatorial layer in the early stage consists of arcuate chambers with basal stolons, and ogival-to spatulate chamberlets with annular and oblique stolons in the later stages. These features are consistent with the phylogenetically advanced members of the Western Tethyan Lepidorbitoides lineage, such as L. minor (Schlumberger) and L. socialis (Leymerie), and all samples were assigned to the transitional development stages of these species based on the morphometry. The taxonomic status of some Lepidorbitoides species, originally described from the Kallankuruchchi Formation and widely adopted in previous works, such as L. blanfordi (Rao) and L. inornata (Rao), are not justified. We extend the geographic range of Western Tethyan Lepidorbitoide s to southern India.